2014
DOI: 10.1016/j.freeradbiomed.2014.08.025
|View full text |Cite
|
Sign up to set email alerts
|

A time course of NADPH-oxidase up-regulation and endothelial nitric oxide synthase activation in the hippocampus following neurotrauma

Abstract: Nicotinamide adenine dinucleotide phosphate oxidase (NADPH-oxidase; NOX) is a complex enzyme responsible for increased levels of reactive oxygen species (ROS), superoxide (O2.−). NOX derived O2.− is a key player in oxidative stress and inflammation mediated multiple secondary injury cascades (SIC) following traumatic brain injury (TBI). The O2.− reacts with nitric oxide (NO), produces various reactive nitrogen species (RNS), and contributes to apoptotic cell death. Following a unilateral cortical contusion, yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 95 publications
1
30
0
Order By: Relevance
“…These findings might thereby not account for the intracellular NO levels within different brain regions. Nevertheless, our findings were supported by studies reporting postinjury increases in NO metabolites, 16,46,47 iNOS activity 17,48,49 or iNOS expression. [50][51][52] Correspondingly, we also observed severity-independent increases in iNOS, but not nNOS mRNA expression at 4 hours in cortex and hippocampus in ipsilateral brain regions.…”
Section: Discussionsupporting
confidence: 86%
“…These findings might thereby not account for the intracellular NO levels within different brain regions. Nevertheless, our findings were supported by studies reporting postinjury increases in NO metabolites, 16,46,47 iNOS activity 17,48,49 or iNOS expression. [50][51][52] Correspondingly, we also observed severity-independent increases in iNOS, but not nNOS mRNA expression at 4 hours in cortex and hippocampus in ipsilateral brain regions.…”
Section: Discussionsupporting
confidence: 86%
“…Our previous studies also showed that oxidative stress in the cerebral tissue occurs as early as 3 h post TBI [4][5][6]. The superoxide producing enzyme (NADPH-oxidase), a known contributor of inflammation and oxidative-stress mediated neurodegeneration [21,64] is up-regulated within 6 h after neurotrauma [7]. The pro-inflammatory cytokine's up-regulation at 48 h [71] and significant loss of synaptic components at 96 h [6] support that "time-post-injury" is an important factor in developing therapeutic strategies after TBI.…”
Section: Discussionmentioning
confidence: 90%
“…Surgical procedure and cortical contusions were made under isoflurane anesthesia (2%) as previously described [7]. Rats were subjected to a unilateral moderate controlled cortical impact (CCI) of 2.0 mm depth at 3.5 m/s and 500 ms dwell time using the TBI 0310, a pneumatic impacting device (Precision Systems & Instrumentation, Fairfax Station, VA) with a hard stop Bimba cylinder (Bimba Manufacturing, Monee, IL).…”
Section: Animals and Surgical Proceduresmentioning
confidence: 99%
See 2 more Smart Citations